Magnetic order and lattice anomalies in the J(1)-J(2) model system VOMoO4 - Bombardi, A; Chapon, L; Margiolaki, I; Mazzoli, C; Gonthier, S; Duc, F; Radaelli, P (2005)
High-resolution x-ray and neutron powder-diffraction measurements were performed on polycrystalline VOMoO4. Below ≃ 40K the system orders in a simple Néel antiferromagnetic state (propagation vector k =0), indicating a dominant role of the nearest-neighbor interactions. The order is three dimensional but the reduced saturated magnetic moment m of 0.41 (1) μ V4+ at 2K indicates strongly two-dimensional character and enhanced quantum fluctuations. On cooling, there is no evidence of a reduction of the crystal symmetry. However, neutron diffraction indicates an anomalous evolution of the lattice parameters, which can be related to the onset of magnetic correlations. © 2005 The American Physical Society.